Kegiatan preservasi preventif dan kuratif koleksi di Perpustakaan Universitas Komputer Indonesia - Nurmustafha, Nida; Damayani, Ninis Agustini; Khadijah, Ute Lies Siti; Rodiah, Saleha; CMS, Samson; Rukmana, Evi Nursanti; Khoerunnisa, Lutfi (Faculty of Communication, Padjadjaran University, 2024)
Collection preservation is a crucial aspect of a library system. A higher education library called the University of Computer Indonesia (Unikom) Library uses preservation to make sure that users can access collections in the future. This study aims to examine the collection preservation activities at the Unikom Library, focusing on the analysis of preventive and curative preservation activities. This research uses a qualitative descriptive method. The findings show that preventive preservation activities at the Unikom Library include educating users, controlling room temperature and humidity, keeping collections away from direct sunlight, installing naphthalene balls on bookshelves, and setting up CCTV, flap barriers, fire extinguishers, smoke detectors, and sprinklers. Meanwhile, curative activities include covering library materials, fumigation by third parties, regular cleaning of rooms and collections, binding library materials, replacing damaged covers or pages of books by third parties, and media conversion (digitization) of thesis collections done using a scanner through the scanning process. This study concludes that both preventive and curative preservation activities at the Unikom Library have been carried out effectively.